Factors related to the incidence of low birth weight - Rahmadani, Maghrisa; Ningrum, Novalia Widiya; Fajriannor TM, M; Maolinda, Winda (Health Sciences International Journal, 2024)
Background: Low birth weight (LBW) remains a significant concern, particularly for newborn mortality in the neonatal period. It serves as a crucial public health indicator for maternal health, nutrition, access to healthcare services, and poverty.  LBW is not solely influenced by pre-pregnancy maternal characteristics, but also by risk factors encountered during pregnancy. Objective: Knowing the factors related to the incidence of low birth weight in laboring mothers. Method: This analytic observational study employed a cross-sectional approach. A sample of 308 mothers giving birth were recruited using purposive sampling at Idaman Hospital, Banjarbaru. Categorical data is systematically presented in a frequency distribution table, and the associations between variables are statistically analyzed using the Chi-square test, utilizing SPSS software for accurate computation and interpretation of results. Results: The results showed that 71.8% of mothers delivering babies were not at risk (20-35 years old), 72.1% were not anemic, 77.3% did not experience pregnancy-induced hypertension, 78.6% did not have premature rupture of membranes and 76% did not deliver LBW babies. Statistical analysis revealed significant relationships between age (p-value = 0.024), anemia (p-value = 0.009), pregnancy-induced hypertension (p-value = 0.014), and premature rupture of membranes (p-value = 0.031) with the incidence of LBW. Conclusion: This study shows the association between age, anemia, pregnancy-induced hypertension, and premature rupture of membranes with the incidence of LBW.